(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
Human language is a social achievement that is subject to changes exerted by the same society. When studying society with their age groups, the sexes of people, the jargon of the different groups, the social classes, we are dealing with the sphere of what is sociolinguistics. Linguistics in Chile begins to develop in the late nineteenth century, with the great protagonist that was Rodolfo Lenz, who is considered the father of the national scientific linguistics. Lenz contributed with two studies to the Castilian language used in Chile. That is why he stands out as one of the leading linguists in Chile. This scientist also analyzed with mastery the social shaping of our people from a linguistic point of view. In this paper, we review how Professor Rodolfo Lenz, besides being the father of linguistics in Chile, is also an unparalleled social visionary and scientific sociolinguist in the country, according to the current perspective.